Preparing Young Minds for Financial Success: Capital Market Literacy at SMA Negeri 1 Medan - Andreani Caroline Barus; Syafira Ulya Firza; Agustina; Iskandar Muda Situmorang; Halim, Fandi (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Financial literacy is essential for younger generation to understand how to manage finances, along with its potential profits and risks involved. This community service activity aimed to improve financial literacy among students of SMA Negeri 1 Medan. The program was conducted through seminars and interactive simulations using Stocklab game, which allow students to learn about stock investments in a fun and practical way. The activity took place over two days, starting with educational sessions on investment, risks, and diversification strategies. The next part involved a capital market simulation by using the Stocklab game. Pre-test and post-test questionnaires were administered to evaluate the students' understanding. The pre-test and post-test results showed a significant improvement in students' understanding of investments and the capital market, including their ability to recognize risks and identify reliable sources of information. In conclusion, the simulation-based capital market literacy education was effective in enhancing students' ability to manage finances and investments, helping them become financially savvy young individuals.